A Prospective, Randomized Comparison of Promus Everolimus-Eluting and TAXUS Liberte Paclitaxel-Eluting Stent Systems in Patients with Coronary Artery Disease Eligible for Percutaneous Coronary Intervention: The PROMISE Study - Kim, Ung; Lee, Chan-Hee; Jo, Jung-Hwan; Lee, Hyun-Wook; Choi, Yoon-Jung; Son, Jang-Won; Lee, Sang-Hee; Park, Jong-Seon; Shin, Dong-Gu; Kim, Young-Jo; Jeong, Myung-Ho; Cho, Myung-Chan; et al. (Journal of Korean medical science, 2013)
We aimed comparing two-year clinical outcomes of the Everolimus-Eluting Promus and Paclitaxel-Eluting TAXUS Liberte stents used in routine clinical practice. Patients with objective evidence of ischemia and coronary artery disease eligible for PCI were prospectively randomized to everolimus-eluting stent (EES) or paclitaxel-eluting stent (PES) groups. The primary end-point was ischemia-driven target vessel revascularization (TVR) at 2 yr after intervention, and the secondary end-point was a major adverse cardiac event (MACE), such as death, myocardial infarction (MI), target lesion revascularization (TLR), TVR or stent thrombosis. A total of 850 patients with 1,039 lesions was randomized to the EES (n=425) and PES (n=425) groups. Ischemic-driven TVR at 2 yr was 3.8% in the PES and 1.2% in the EES group (P for non-inferiority=0.021). MACE rates were significantly different; 5.6% in PES and 2.5% in EES (P = 0.027). Rates of MI (0.8% in PES vs 0.2% in EES, P = 0.308), all deaths (1.5% in PES vs 1.2% in EES, P = 0.739) and stent thrombosis (0.3% in PES vs 0.7% in EES, P = 0.325) were similar. The clinical outcomes of EES are superior to PES, mainly due to a reduction in the rate of ischemia-driven TVR.